TATA KELOLA ASET BERGERAK DI KABUPATEN KUANTAN SINGINGI (STUDI KASUS PENATAAN ALAT ANGKUTAN DAN ALAT-ALAT BERAT PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG) - Habri Ustila; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Regional assets are an important resource for local government as the main pillar of original income, therefore it is important for local governments to adequately manage local assets. In this study the authors limit the assets of the regions in question are movable assets in the form of transportation equipment and heavy equipment of the public works and spatial planning, moving assets in the form of equipment and heavy equipment needs special attention in the governance or management, related to the asset management according to Sugiama (2013:15) interpreted as a science and art to guide wealth management that includes the process of planning the asset needs, obtaining inventory, performing legal audits, appraising, operating, maintaining, renewing or eliminating to transfer assets effectively and efficiently. This study aims to describe the management of moving assets in the form of transportation equipment and heavy equipment at the office work general and spatial planning of kuantan singing regency as well as factors affecting the governance of assets. The method used is qualitative descriptive data collection by observation, interview and documentation. The result of the study describe that the governance of moving assets on the public works department and spatial planning of kabupaten kuantan singing regency there are weaknesses in the planning for budget maintenance and maintenance of asset and standard operating procedures in the implementation of asset governance. Factual factors that influence the governance of assets, human resources, budgeting and standard operating procedures in asset asset settlement.Keywords: Management, Asset, Assets Management